Death and the American South - Friend, Craig Thompson; Glover, Lorri, 1967- (Cambridge : Cambridge University Press, 2014)
"This rich collection of original essays illuminates the causes and consequences of the South's defining experiences with death. Employing a wide range of perspectives, while concentrating on discrete episodes in the region's past, the authors explore topics from the seventeenth century to the present, from the death traps that emerged during colonization to the bloody backlash against emancipation and civil rights to recent canny efforts to commemorate - and capitalize on - the region's deadly past. Some authors capture their subjects in the most intimate of moments: killing and dying, grieving and remembering, and believing and despairing. Others uncover the intentional efforts of Southerners to publicly commemorate their losses through death rituals and memorialization campaigns. Together, these poignantly told Southern stories reveal profound truths about the past of a region marked by death and unable, perhaps unwilling, to escape the ghosts of its history. Craig Thompson Friend is Professor of History and Director of Public History at North Carolina State University. Lorri Glover is the John Francis Bannon Endowed Chair in the department of history at St. Louis University"--
Death and the American South : an introduction / Craig Thompson Friend and Lorri Glover -- Mutilated bodies, living specters : scalpings and beheadings in the early South / Craig Thompson Friend -- The usable death : evangelicals, Anglicans, and the politics of dying in the late colonial low country / Peter N. Moore -- When 'history becomes fable instead of fact' : the deaths and resurrections of Virginia's leading revolutionaries / Lorri Glover -- American mourning : catastrophe, public grief, and the making of civic identity in the early national South / Jewel L. Spangler -- To claim one's own : death and the body in the daily politics of antebellum slavery / Jamie Warren -- Nativists and strangers : yellow fever and immigrant mortality in antebellum Charleston, South Carolina / Jeff Strickland -- 'Cumberer of the earth' : suffering and suicide among the faithful in the Civil War South / Diane Miller Sommerville -- The 'translation' of Lundy Harris : interpreting death out of the confusion of sexuality, violence, and religion in the New South / Donald G. Mathews -- 'He's only away' : condolence literature and the emergence of a modern South / Kristine M. McCusker -- 'A monument to Judge Lynch' : racial violence, symbolic death, and black resistance in Jim Crow Mississippi / Jason Morgan Ward -- Reframing the Indian dead : removal-era Cherokee graves and the changing landscape of Southern memory / Andrew Denson.
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Death -- Social aspects -- United States; Mourning customs -- United States; Bereavement -- United States; Southern States -- Social life and customs; Southern States -- History; Mort -- Aspect social -- États-Unis.; Deuil -- Coutumes -- États-Unis.; Deuil -- États-Unis.; États-Unis (Sud) -- Histoire; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; Bereavement; Death -- Social aspects; Manners and customs; Mourning customs; Southern States; United States; History